2016
DOI: 10.1007/s11947-016-1703-4
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Functional Wrapping Design by Complexation of ε-Polylysine with Liposomes Entrapping Bioactive Peptides

Abstract: An innovative edible wrapping with potential use for designing functional foods with antimicrobial capacity was developed by complexation of ε-polylysine with peptideloaded liposomes. Unmarketable long-term frozen cooked shrimp (L. vannamei) muscle was used as a source of both bioactive peptides and complex liposomal suspension carrier, producing a sustainable value-added protein wrapping material with desirable sensory properties. A <10 kDa peptide fraction (SH) with antioxidant and angiotensin-converting enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Montero et al (2019) found no significant differences in the thickness of liposome-containing sodium caseinate films, both empty and filled with a <1 kDa peptide fraction, but they observed a slight increase in film density as a result of the incorporation of liposomes. In cooked shrimp myofibrillar protein film containing liposomes filled with protein hydrolysate (<10 kDa), Alemán et al (2016) did not find differences in thickness due to the presence of liposomes. Both cases were protein films, although the molecular weights of the biopolymers were very different, and in the second case with a high degree of aggregation.…”
Section: Physical Propertiesmentioning
confidence: 61%
“…Montero et al (2019) found no significant differences in the thickness of liposome-containing sodium caseinate films, both empty and filled with a <1 kDa peptide fraction, but they observed a slight increase in film density as a result of the incorporation of liposomes. In cooked shrimp myofibrillar protein film containing liposomes filled with protein hydrolysate (<10 kDa), Alemán et al (2016) did not find differences in thickness due to the presence of liposomes. Both cases were protein films, although the molecular weights of the biopolymers were very different, and in the second case with a high degree of aggregation.…”
Section: Physical Propertiesmentioning
confidence: 61%
“…Tannin-containing liposomal nanosuspensions (TLS) were prepared using the heating/homogenization method with lamellarity and size reduction by ultrasound cycles [ 38 ]. To prepare 100 mL of TLS [1 mg/mL], 0.1 g of condensed tannins obtained from green grape seeds (Sauvignon blanc variety) were dissolved in 20 mL of a solution (50:50% v / v ) of ethanol-citrate buffer (0.1 M at pH 3) at 70 ± 1 °C and 700 rpm, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Hydrophilic antioxidant activity was measured by the ABTS* radical method according to Alemán et al [ 24 ]. ABTS* radical solution was prepared by diluting ABTS (2,2′-Azino-bis(3-ethylbenzthiazoline-6-sulfonic acid)) in a solution of 2.45 mM K 2 S 2 O 8 up to a concentration of 7 mM; the subsequent solution was left in darkness at room temperature for 16 h and then adjusted to 0.7 absorbance at 734 nm.…”
Section: Methodsmentioning
confidence: 99%